Leadership Competence in Professional Training of Science Teachers: Guidelines and International Practices - Kolomiiets, Alla (Pedagogical Discourse, 2025)
The contemporary higher education system is undergoing profound transformations driven by rapid advances in science, technology, digital tools, and global challenges. In Ukraine, these changes are complicated by wartime conditions, prolonged distance learning, and migration, creating gaps in educational quality. Addressing these challenges requires not only skilled practitioners but also competent academic leaders capable of guiding educational communities, fostering innovation, and managing organizational processes. This study investigates the formation of leadership competencies among higher education teachers of natural sciences, emphasizing the need for all educators to develop leadership skills, regardless of formal managerial roles. A combination of theoretical, qualitative, and quantitative methods was applied. Literature review and systematization of national and international sources helped define the structure and content of leadership competencies. Qualitative methods, including content analysis, thematic coding, and a three-round Delphi survey with 15 experts, identified seven core components: strategic, communicative-linguistic, organizational-managerial, research-innovative, ethical-social, emotional-reflexive, and professional development and mentoring. Quantitative surveys of 36 teachers and 65 students revealed that most educators (58.3 %) and students (56.9 %) recognize the need to develop leadership competencies, preferring practical, context-based learning. The findings highlight the critical role of leadership competencies in ensuring educational quality, fostering research culture, and creating innovative academic environments. The study provides evidence-based recommendations for integrating leadership development into natural sciences programs through mentoring, experiential learning, and interdisciplinary collaboration. These results support forming a new generation of academic leaders in Ukraine, ready to meet contemporary educational challenges and foster sustainable development in academic communities.